Visceral pain and sensitisation in women with dysmenorrhea: a narrative review - Naia, Zeltia; Patiño-Núñez, Sergio; Bello, Olalla (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Visceral pain (VP), from internal organs, is one of the main reasons for health consultations and represents a source of chronic pain. It can provoke referred musculoskeletal pain, viscero-somatic pain, hyperalgesia, and allodynia. The objective of this nar-rative review is to analyse the underlying mechanisms of somatic reﬂexed VP and viscero-visceral sensitisation processes that can occur in women with dysmenorrhea. The aﬀectation of one viscera can lead to a sensitisation in those where metameric innervation is shared. In women with dysmenorrhea and painful menstrual periods, some studies ﬁnd a concomitance increase in gastrointestinal pathologies. VP is a source of chronic pain, that favours the perception of referred pain in tissues where metameric innervation is shared. Women with dysmenorrhea have more possibilities to develop gastrointestinal pathologies like irritable bowel syndrome.
Keywords: visceral pain; referred pain; dysmenorrhea